Estudo exploratorio dos problemas, nos seus aspectos físicos, apresentados por pacientes no pós-operatório imediato: uma contribuição ao processo de enfermagem. - Kruse, Maria Henriqueta Luce (1980)
The purpose here in this paper was to identify che problems in their physical aspects , presenteei by the patients during their immcdiate post-operatory period with the aim of organizing a nursing post-operatory flowsheet. The method aimed was the patient-physical examination. An assessment of the problems identified in six areas was also performed, which are related to the body segments examined. These areas were called general appearance, vital signs, head and neck, upper limbs, trunk and lower limbs. 100 patients were examined and 1.246 problems Were identified. The head and neck area had a greater incidence of problems followed by the area of general appearance. A nursing post-operatory flowsheet is presented at the conclusion of this paper; this sheet becomes a patient-assessment tool at the moment of admission to the Recovery-room. This tool may be used by the nurse with the goal of providing assistence to this kinds of patient.